2020
DOI: 10.1007/s10120-020-01132-x
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of nontyphoidal salmonellosis in gastric cancer: a nationwide matched cohort study

Abstract: BackgroundThe research is to explore the association between nontyphoidal salmonellosis (NTS) and subsequent gastric cancer. Methods We conducted a retrospective study by analyzing hospitalization dataset from the National Health Insurance Research Database in Taiwan. Patients aged 20 years and older with NTS (n = 9 097) admitted between January 1, 2000, and December 31, 2012, were enrolled and followed up until December 31, 2013. The primary outcome was the incidence of gastric cancer. Cox proportional hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…enterica serotype Typhimurium in an experimental setting using murine gallbladder organoids ( Scanu et al, 2015 ). Seven epidemiological articles were found assessing the association between NTS infection and colorectal ( n = 3), CC ( n = 2), biliary tract cancer ( n = 2), and gallbladder, gastric, liver, and pancreatic cancer (latter four: n = 1) ( Supplementary Table 12 ; Kato et al, 2013 ; Iyer et al, 2016 ; Lu et al, 2017 ; Mughini-Gras et al, 2018 ; De Savornin Lohman et al, 2020 ; Chang et al, 2021 ; Duijster et al, 2021 ). The humoral immune response against Salmonella flagellin in CRC patients and individuals with colorectal polyps versus healthy controls was assessed in two different cohorts ( Supplementary Table 12 ; Kato et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…enterica serotype Typhimurium in an experimental setting using murine gallbladder organoids ( Scanu et al, 2015 ). Seven epidemiological articles were found assessing the association between NTS infection and colorectal ( n = 3), CC ( n = 2), biliary tract cancer ( n = 2), and gallbladder, gastric, liver, and pancreatic cancer (latter four: n = 1) ( Supplementary Table 12 ; Kato et al, 2013 ; Iyer et al, 2016 ; Lu et al, 2017 ; Mughini-Gras et al, 2018 ; De Savornin Lohman et al, 2020 ; Chang et al, 2021 ; Duijster et al, 2021 ). The humoral immune response against Salmonella flagellin in CRC patients and individuals with colorectal polyps versus healthy controls was assessed in two different cohorts ( Supplementary Table 12 ; Kato et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, this may dilute the observed effect of NTS in risk estimates including the older age groups. In a Taiwanese cohort, a HR of 1.03 (95% CI 0.72–1.47) was reported for the combined risk of colon and rectum cancer, while an over twofold significantly increased risk of GC was observed ( Supplementary Table 12 ; Chang et al, 2021 ). In addition, also an increased risk of developing biliary tract cancer after salmonellosis was reported in both a Dutch study (SIR: 1.53; 95% CI 0.70–2.91) and the Taiwanese cohort (HR: 2.23; 95% CI 0.83–6.05), though numbers were low in both studies ( De Savornin Lohman et al, 2020 ; Chang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A matched control was assigned to each case with a cholecystectomy according to age, sex, index date, occupation and propensity score. We used the propensity score‐matching method to account for baseline differences 18 . The observed covariates in the logistic regression model to generate the propensity score were hypertension (ICD9 codes: 401‐405), diabetes (ICD9 code: 250), hyperlipidaemia (ICD9 codes: 272), coronary artery disease (ICD9 codes: 410‐414), cerebrovascular accident (430‐438), chronic kidney disease (ICD9 code: 585), chronic obstructive pulmonary disease (COPD, ICD9 codes: 491, 492 and 496), chronic liver diseases (ICD9 code: 571.4), autoimmune diseases (including systemic lupus erythematosus, ICD9 code: 710.0; ankylosing spondylitis, ICD9 code: 720.0; rheumatoid arthritis, ICD‐9‐CM code: 714.0; Sjögren's syndrome, ICD‐9‐CM code: 710.2), psoriasis (ICD9 code: 696), vasculitis (ICD9 code: 446) and inflammatory bowel disease (IBD, including Crohn's disease, ICD9 codes: 555.x and ulcerative colitis, ICD9 codes: 556.x).…”
Section: Methodsmentioning
confidence: 99%
“…NHIRD is available for research purposes with appropriate applications. The validity of NHIRD for use in epidemiological cancer research has been shown in the previous publication (17)(18)(19)(20)(21)(22)(23)(24). NHIRD includes patients treated at dedicated veterans' hospitals.…”
Section: Data Sourcesmentioning
confidence: 98%